Business Strategy Analysis at PT. Kapitol Era Mas Using The Business Model Canvas and Swot Method Approaches (Case Study: “Coklat Mimpi” Franchise Business Unit) - RIZQI, Miftahur; ARDIANSAH, Irfan (PT Keberlanjutan Strategis Indonesia, 2024)
The rapid development of the modern lifestyle opens great opportunities in the culinary sector, which continues to grow, including in South Tangerang City. This study analyzes the business strategy of the “Coklat Mimpi